PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2009 – 2011 - Supriatna, Nono; Triantoro, Arvian (Program Studi Akuntansi FPEB UPI, 2013)
The research aims to examine the influence of intellectual capital to company’s financial performance (profitability, productivity, and market valuation. Profitability measured by Return On Asset (ROA), productiviy measured by Asset Turn Over (ATO), and market valuation measured by Market to Book Value (MB). Independent variabel used in this research is intellectual capital which measured by VAIC™, while dependent variable are ROA, ATO, and MB. In this research, the authors used a quantitative verificative. Data obtainable from retail company listed in Indonesia Stock Exchange (IDX) year period 2009-2011. The samples in this research using the method of purposive. Based on sampling criteria the final sample in this research is 7 retail companies. This research use simple linear regression for data analysis. From the research that has been done shows that intellectual capital has positive influence to profitability, intellectual capital has negative influence to productivity, and intellectual capital has no effect to market valuation.